answersLogoWhite

0


Best Answer

8

User Avatar

Mabelle McDermott

Lvl 10
3y ago
This answer is:
User Avatar
More answers
User Avatar

Wiki User

7y ago

That's already pretty simple. It can be factored to 2(3x - 1)

This answer is:
User Avatar

User Avatar

Wiki User

7y ago

It is 2*(3x - 1).

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is 6x-2 simplified?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 3x-5x plus x2-6x2 simplified?

(3x - 5x) + (x2 - 6x2) = -2x -5x2 = -x(2 + 5x)


What is 4x2-x plus 2x2?

4x2-x+2x2 is 6x2-x when simplified


What is the answer to 9 plus 6x2?

9+6x2=21


6x2 plus 32x plus 12-4x-3x2-36?

6x^2 +32x +12 -4x -3x^2 -36 = 3x^2 +28x -24 simplified


Area is 36x4-64x2 width is 6x2-8x what is the length in terms of x?

Area 36x4-64x2 and width is 6x2-8x Area = Length * width36x4 -64x2 = L * 6x2 -8x(36x4 -64x2) / (6x2 -8x) = L(36x4 -64x2) / (6x2 -8x) = L((6x2 -8x)2 + 96x3)/ (6x2 -8x) = L1 + 96x3/ (6x2 -8x) = L1 + 96x3/ x(6x -8) = L1 + 96x2/ (6x -8) = L


What is the answer to 6x2-9x-6?

6x2-9x-6 is equal to 66.


What is a factor of 6x2 17x plus 12?

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)


How do you factor 6x2 plus 2x-28?

6x2=12 2x-28=?


How do you factor 6x2 plus 10x?

6x2 + 10x = 2x(3x + 5)


What is 6x2 in meters?

6x2 is a multiplication operation that equals 12. It does not have a unit of measurement such as meters.


What is the factor of 6x2 13x-5?

To find the factors of the quadratic expression 6x^2 + 13x - 5, we need to factorize it into two binomial expressions. We can do this by finding two numbers that multiply to the coefficient of x^2 (6) multiplied by the constant term (-5), which is -30, and add up to the coefficient of x (13). These numbers are 15 and -2. Therefore, the factored form of the expression is (2x + 5)(3x - 1).


What are the factor of 6x2 plus 7x-5?

6x2 + 7x - 5 = (3x + 5)(2x - 1)